Psychological morbidity among adults with cerebral palsy and spina bifida. Issue 4 (27th March 2021) - Peterson, Mark D.; Lin, Paul; Kamdar, Neil; Mahmoudi, Elham; Marsack-Topolewski, Christina N.; Haapala, Heidi; Muraszko, Karin; Hurvitz, Edward A.
Abstract: Background: Very little is known about the risk of developing psychological morbidities among adults living with cerebral palsy (CP) or spina bifida (SB). The objective of this study was to compare the incidence of and adjusted hazards for psychological morbidities among adults with and without CP or SB. Methods: Privately insured beneficiaries were included if they had an International Classification of Diseases, Ninth revision, Clinical Modification diagnostic code for CP or SB ( n = 15 302). Adults without CP or SB were also included ( n = 1 935 480). Incidence estimates of common psychological morbidities were compared at 4-years of enrollment. Survival models were used to quantify unadjusted and adjusted hazard ratios for incident psychological morbidities. Results: Adults living with CP or SB had a higher 4-year incidence of any psychological morbidity (38.8% v. 24.2%) as compared to adults without CP or SB, and differences were to a clinically meaningful extent. Fully adjusted survival models demonstrated that adults with CP or SB had a greater hazard for any psychological morbidity [hazard ratio (HR): 1.60; 95% CI 1.55–1.65], and all but one psychological disorder (alcohol-related disorders), and ranged from HR: 1.32 (1.23, 1.42) for substance disorders, to HR: 4.12 (3.24, 5.25) for impulse control disorders. Conclusions: Adults with CP or SB have a significantly higher incidence of and risk for common psychological morbidities, as compared to adults without CP or SB. Efforts are needed to facilitate the development of improved clinical screening algorithms and early interventions to reduce the risk of disease onset/progression in these higher-risk populations.